Cover Feature: Growth of ZIF‐8 MOF Films with Tunable Porosity by using Poly (1‐vinylimidazole) Brushes as 3D Primers (Chem. Eur. J. 54/2020). Issue 54 (2nd September 2020) - Allegretto, Juan A.; Iborra, Agustín; Giussi, Juan M.; von Bilderling, Catalina; Ceolín, Marcelo; Moya, Sergio; Azzaroni, Omar; Rafti, Matias
Abstract : ZIF‐8 (based on Zn and 2‐methylimidazole) MOF film growth can be controlled by using SI‐ATRP‐synthesized polymeric brushes as 3D primers. This strategy relies on the inclusion of chemical moieties in the brush, which are compatible with MOF chemical structure. According to such criteria, Poly(1‐vinylimidazole) brushes with increasingly higher grafting densities were selected. Aside from the inherently hydrophobic microporosity arising from ZIF‐8 structure, our approach renders control over the proportion of constructional mesoporosity, which allow differential adsorption. More information can be found in the Full Paper by O. Azzaroni, M. Rafti, et al. on page 12388 .